THE CONCEPTS OF CONTEXTUAL INTERPRETATION OF THE QUR’AN ABDULLAH SAEED - Nabila Fajriyanti Muhyin (Sekolah Tinggi Agama Islam Sadra, 2023)
Along with the demands of modern and contemporary times, Muslim thinkers and scientists are starting to try, to respond, and find solutions to the crisis of how religious traditions are still able to relate to modernity and changing times in general. This article discusses one of the approaches used by contemporary scholars in understanding the Qur’an, one of whom is Abdullah Saeed, a professor of Islamic studies in Australia, who initiated the method of contextualizing the Qur’an. In particular, the author tries to explain methodological aspects from Abdullah Saeed’s point of view in contextualizing the Qur'an. To be able to find answers to these problems, the author tries to collect data from various sources, both primary sources, namely from Abdullah Saeed’s writings, and secondary sources, namely writings related to the main focus. To conclude, the writer tries to analyze the data that has been collected using the theory of character studies by analyzing the environment around the characters and the arguments that are built. The author concludes that the contextual interpretation initiated by Abdullah Saeed is a method of interpreting the text of the verses of the Qur’an which is related to the context of life and conditions society to answer various problems experienced by contemporary society today. Apart from that, in his thinking, Abdullah Saeed has the advantage of the double movement method initiated by Fazlur Rahman, namely he can provide systematic and operational steps in contextualizing the Qur’an.